The healing power of ginseng - Hou, Joseph P., 1929- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
Health and medical uses of ginseng is broad due to its adaptogenic properties, it is an effective tonic. Ginseng can be used to improve mental and physical performance, reduce stress, and increase longevity. This book covers the properties and uses of four varieties of ginseng in the world with focus on American and Asian types of ginseng. This books discusses healing properties of ginseng, growing ginseng plants, chemical, nutritional, medical and pharmacological properties, detoxification, longevity and proper usage of the root.
OCLC-licensed vendor bibliographic record.
Keywords: Ginseng -- Therapeutic use; HEALTH & FITNESS / Herbal Medications; MEDICAL / Nutrition; SCIENCE / Chemistry / General